The protective variant rs7173049 at LOXL1 locus impacts on retinoic acid signaling pathway in pseudoexfoliation syndrome. (15th April 2019) - Berner, Daniel; Hoja, Ursula; Zenkel, Matthias; Ross, James Julian; Uebe, Steffen; Paoli, Daniela; Frezzotti, Paolo; Rautenbach, Robyn M; Ziskind, Ari; Williams, Susan E; Carmichael, Trevor R; Ramsay, Michele; et al.
Abstract: LOXL1 (lysyl oxidase-like 1) has been identified as the major effect locus in pseudoexfoliation (PEX) syndrome, a fibrotic disorder of the extracellular matrix and frequent cause of chronic open-angle glaucoma. However, all known PEX-associated common variants show allele effect reversal in populations of different ancestry, casting doubt on their biological significance. Based on extensive LOXL1 deep sequencing, we report here the identification of a common non-coding sequence variant, rs7173049A>G, located downstream of LOXL1, consistently associated with a decrease in PEX risk (odds ratio, OR = 0.63; P = 6.33 × 10 −31 ) in nine different ethnic populations. We provide experimental evidence for a functional enhancer-like regulatory activity of the genomic region surrounding rs7173049 influencing expression levels of ISLR2 (immunoglobulin superfamily containing leucine-rich repeat protein 2) and STRA6 [stimulated by retinoic acid (RA) receptor 6], apparently mediated by allele-specific binding of the transcription factor thyroid hormone receptor beta. We further show that the protective rs7173049-G allele correlates with increased tissue expression levels of ISLR2 and STRA6 and that both genes are significantly downregulated in tissues of PEX patients together with other key components of the STRA6 receptor-driven RA signaling pathway. siRNA-mediated downregulation of RA signaling induces upregulation of LOXL1 and PEX-associated matrix genes in PEX-relevant cell types. These data indicate that dysregulation of STRA6 and impaired retinoid metabolism are involved in the pathophysiology of PEX syndrome and that the variant rs7173049-G, which represents the first common variant at the broad LOXL1 locus without allele effect reversal, mediates a protective effect through upregulation of STRA6 in ocular tissues.